Examination of Coliform and Escherichia coli Contamination in Refilled Drinking Water in Cirebon Regency, Indonesia - Ana Naela Shonia; Hikmah Fitriani; Mohammad Erwin Indrakusuma (GHMJ (Global Health Management Journal))
Background: Refillable drinking water is a commonly used source of water for the public. Contamination of this water can lead to various diseases, including waterborne diarrhea. Coliform bacteria and Escherichia coli are indicators of faecal contamination and can cause waterborne diseases. This study aims to determine whether Coliform and Escherichia coli are present in refillable drinking water in Cirebon Regency.